Progressive Cerebral Injury in the Setting of Chronic HIV Infection and Antiretroviral Therapy - Gongvatana, Assawin (2013)
BACKGROUND: Emerging evidence suggests that CNS injury and neurocognitive impairment persist in the setting of chronic HIV infection and combination antiretroviral therapy (CART). Yet whether neurological injury can progress in this setting remains uncertain. METHODS: Magnetic resonance spectroscopy, neurocognitive and clinical assessments were performed over two years in 226 HIV-infected individuals on stable CART, including 138 individuals who were neurocognitively asymptomatic (NA). Concentrations of N-acetylaspartate (NAA), creatine (Cr), choline (Cho), myoinositol (MI), and glutamate/glutamine (Glx) were measured in the midfrontal cortex (MFC), frontal white matter (FWM) and basal ganglia (BG). Longitudinal changes in metabolite levels were determined using linear mixed effect models, as were metabolite changes in relation to global neurocognitive function. RESULTS: HIV-infected subjects showed significant annual decreases in brain metabolite levels in all regions examined, including NAA (2.95%), Cho (2.61%) in the FWM; NAA (1.89%), Cr (1.84%), Cho (2.19%) and Glx (6.05%) in the MFC; and Glx (2.80%) in the BG. Similar metabolite decreases were observed in the NA and subclinically impaired subgroups, including subjects with virologic suppression in plasma and CSF. Neurocognitive decline was associated with longitudinal decreases in Glx in the FWM and the BG, and in NAA in the BG. CONCLUSIONS: Widespread progressive changes in the brain, including neuronal injury, occur in chronically HIV-infected persons despite stable antiretroviral treatment and virologic suppression and can lead to neurocognitive declines. The basis for these findings is poorly understood and warrants further study.